Effects of NAD at purine receptors in isolated blood vessels - Alefishat, Eman; Alexander, Stephen P.H.; Ralevic, Vera (Springer Verlag, 2015)
Nicotinamide adenine dinucleotide (NAD) belongs to the family of naturally occurring adenine dinucleotides, best known for their various intracellular roles. However, there is evidence that they can also be released from cells to act as novel extracellular signalling molecules. Relatively little is known about the extracellular actions of NAD, especially in the cardiovascular system. The present study investigated the actions of NAD in the rat thoracic aorta, porcine coronary artery and porcine mesenteric arteries, mounted in organ baths for isometric tension recording. In the rat thoracic aorta and porcine coronary artery, NAD caused endothelium-independent concentration-dependent vasorelaxations which were unaffected by palmitoylCoA, a P2Y1 receptor antagonist, but which were blocked by CGS15943, a non-selective adenosine receptor antagonist. In the porcine coronary artery, NAD-evoked relaxations were abolished by SCH58261, a selective A2A receptor antagonist. In the rat thoracic aorta, NAD-evoked relaxations were attenuated by A2A receptor antagonism with SCH58261 but were unaffected by an A2B receptor antagonist, MRS1754. In contrast, in the porcine mesenteric artery, NAD-evoked endothelium-independent contractions, which were unaffected by a P2 receptor antagonist, suramin, or by NF449, a P2X1 receptor antagonist, but were attenuated following P2X receptor desensitisation with αβ-meATP. In conclusion, the present results show that NAD can alter vascular tone through actions at purine receptors in three different arteries from two species; its molecular targets differ according to the type of blood vessel.